(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Social health insurance (SHI) is a risk-sharing method-based health care financing and administration. SHI combines the contributions of people, households, businesses, and the government with people’s health hazards. As a result, it shields people from financial and physical hardship and is a generally equitable way to pay for medical care. This study aims to assess the status of social health insurance in Nepal. MATERIALS AND METHODS: The research is based on a review of empirical studies, reports, and data. The Google Scholar search engine was used to locate research publications on health insurance. The Google Scholar Open Database was applied to find the publications using the keywords "health insurance" or "social health insurance in Nepal." All papers that were published before July 2022 were checked for the study. Fifty-seven research papers were discovered during the initial inquiry; five duplicate articles were eliminated, and seven were out of the norm. Finally, 45 research papers and reports were selected for evaluation with the study titled "The status of health insurance in Nepal." RESULTS: This study finds that Madhesh province has poor status (4.63%) of social health insurance and province one has the highest (33.02%) of insured persons in Nepal. Females (52%) insured are higher than males (48%). The population covered by health insurance is seven percent in Nepal. Likewise, the renewal status of social health insurance is poor in Karnali province (50%) and highest in Lumbini province (85%) for the fiscal year 2021/22. CONCLUSIONS: Social health insurance is an effective strategy for fair access to healthcare services. The penetration of social health insurance is low in Nepal. Since the social health insurance program is one of the effective tools for improving the health system in developing nations like Nepal, so the government should speed up its implementation to achieve the goal of universal health coverage and sustainable development goals.